Managing the protein folding demands in the endoplasmic reticulum of plants. Issue 2 (14th March 2016) - Liu, Jian‐Xiang; Howell, Stephen H.
Summary: Endoplasmic reticulum (ER) stress occurs in plants during certain developmental stages or under adverse environmental conditions, as a result of the accumulation of unfolded or misfolded proteins in the ER. To minimize the accumulation of misfolded proteins in the ER, a protein quality control (PQC) system monitors protein folding and eliminates misfolded proteins through either ER‐associated protein degradation (ERAD) or autophagy. ER stress elicits the unfolded protein response (UPR), which enhances the operation in plant cells of the ER protein folding machinery and the PQC system. The UPR also reduces protein folding demands in the ER by degrading mRNAs encoding secretory proteins. In plants subjected to severe or chronic stress, UPR promotes programmed cell death (PCD). Progress in the field in recent years has provided insights into the regulatory networks and signaling mechanisms of the ER stress responses in plants. In addition, novel physiological functions of the ER stress responses in plants for coordinating plant growth and development with changing environment have been recently revealed.